PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA SD - Nurhanurawati; Gito Ronaldo; Abdul Haris; Jufri Saputra; Fatkhur Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to develop Mathematics Worksheets (LKPD) based on Problem-Based Learning (PBL) for the topic of Plane Geometry for fifth-grade students in elementary school. The development of Mathematics LKPD is driven by the need for learning tools that can enhance students' problem-solving abilities, critical thinking skills, and curiosity. This study aims to develop Problem-Based Learning (PBL) Worksheets (LKPD) to improve students' critical thinking skills that are valid, practical, and effective. The research method used is Research and Development (R&D). The steps in conducting this research follow the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study include 2 content experts, 2 media experts, 2 language experts, a teacher, and 32 fifth-grade students from SDN Baru Ranji. The results of the study show that the content expert validation obtained a score of 85%, which falls into the valid category. Media expert validation obtained a score of 87%, also in the valid category. Language expert validation obtained a score of 82%, categorized as valid. It was found that the sig. (2-tailed) value was 0.000 < 0.05, thus Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a significant difference between the pretest and posttest scores of the students, indicating that the use of PBL-based LKPD has an effect on improving the understanding of concepts among fifth-grade students at SDN Baru Ranji. The results of this research are expected to contribute to the improvement of the quality of education in elementary schools.   Keywords: LKPD, mathematics, problem based learning